2008
DOI: 10.1111/j.1742-4658.2008.06713.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine toxins and the cytoskeleton: azaspiracids

Abstract: The azaspiracids (AZAs) are a group of marine phycotoxins discovered during the second half of the 1990s. Several cases of human intoxication due to the presence of AZAs in shellfish have been reported, with gastrointestinal symptoms. Toxicological studies in vivo and in vitro have revealed that various cell types are sensitive to AZA toxicity; however, the biological target of the toxin is still unknown. One of the in vitro signs of AZA toxicity is the alteration of the actin cytoskeleton arrangement, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…This effect is consistent with the in vivo effects inducing complete degradation of gastrointestinal lining and confirmed by TEER experiments on monolayer Caco2 model [30] or by disturbance of filament organization in Caco2 cells [31]. Even if some data indicated that AZA1 induced the fragmentation of E-cadherin [21] and inhibited endocytosis [32], its molecular target is still unknown.…”
Section: Dose-response Relationship and Ic 50 Valuessupporting
confidence: 89%
See 2 more Smart Citations
“…This effect is consistent with the in vivo effects inducing complete degradation of gastrointestinal lining and confirmed by TEER experiments on monolayer Caco2 model [30] or by disturbance of filament organization in Caco2 cells [31]. Even if some data indicated that AZA1 induced the fragmentation of E-cadherin [21] and inhibited endocytosis [32], its molecular target is still unknown.…”
Section: Dose-response Relationship and Ic 50 Valuessupporting
confidence: 89%
“…The human HepG2 hepatocarcinoma cell line (ATCC HB8065, passages [15][16][17][18][19][20][21][22][23][24][25] and the human Caco2 colorectal adenocarcinoma cell line (ATCC HTB-37, passages were cultured in MEM-Glutamax containing 1 g/l glucose and supplemented with 10 % fetal calf serum (FCS), 50 U/mL penicillin and 50 μg/mL streptomycin, and 1 % nonessential amino acids. The mouse Neuro2a neuroblastoma cell line (ATCC CCL-131, passages 11-50) was cultured in RPMI 1640-Glutamax containing 2 g/l glucose and supplemented with 10 % FCS, 1 mM sodium pyruvate, 50 U/mL penicillin, and 50 μg/mL streptomycin.…”
Section: Cell Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…8 In vivo studies in mice exposed to AZA1 revealed severe effects such as deformation of intestinal epithelial villi 9, 10 as well as damage to T and B lymphocytes, accumulation of fatty acid deposits in the liver, increased prevalence of lung tumors, and hyperplasia within the stomach lining. 11, 12 In vitro studies have shown the AZAs to be highly cytotoxic causing a variety of cytoskeletal effects 13-18 and stimulation of cAMP production and cytosolic calcium release. 19, 20 In spinal cord neurons, AZA1 was shown to inhibit bioelectrical activity through a mechanism that was independent of voltage-gated sodium (Na + ) or calcium (Ca 2+ ) current.…”
Section: Introductionmentioning
confidence: 99%
“…Toxin that this species produce is called azaspiracid. It have been described that effects of azaspiracids could be related to cytoskeletal changes, such as E-cadherin degradation, caspase activation / apoptosis, membrane cholesterol reduction, or gene expression alterations (Vilarino, 2008). The highest content of this toxin is accumulation in digestive gland (James et al, 2008).…”
Section: Azaspiracid Shellfish Poisoningmentioning
confidence: 99%